Evaluación de metodologías de análisis multicriterio para toma de decisiones en proyectos de estructuras en acero (2017)
This project developed in detail the evaluation of multicriteria analysis methodologies in the decision making process in steel construction projects, specifically in the choice of their structural system due to it is importance in the later stages of design. Simultaneously, the general and specific factors that are taken into account to choose the best configuration for a given architectural plant. Additionally, it studies the correlation between these factors and the conclusions about them.--Tomado del Formato de Documento de Grado.